Thanks for the Memories - Dunlap, Ariana; Stenzel, Carlie; Rogers, Matthew; Nyhart, Rachel; Butler, Christopher; Lynch, Bridget (My University, 2016)
Credits: Kay and Roger Shanks, Ariana Dunlap, Carlie Stenzel, Matthew Rogers, Rachel Nyhart, Christopher Butler, Bridget Lynch.
Citation: Digital Ethnography. (2016). Thanks for the Memories. K-State 48 Film Festival, 2016
Keywords: Digital Ethnography; K-State 48 Film Festival